PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN TAMAN WISATA ALAM TELAGA WARNA KABUPATEN BOGOR PROVINSI JAWA BARAT - Ajeng Aspuan; Rizki Nurul Nugraha (Sekolah Tinggi Pariwisata Mataram, 2022)
The existency of conservation areas and surrounding communities is an inseparable part. The interaction of the people with the forest area is influenced by the perception of local community surrounding the forest. This study was aimed to describe the community's knowledge about the Nature Tourism Park (NTP) and community perceptions of the management of NTP. This research was conducted in May - June 2020 in Tugu Utara Village, Cisarua District, Bogor. Data obtained through field observations, interviews, questionnaires and literature studies, and were analyzed quantitatively by describing the percentage.